2019
DOI: 10.1371/journal.pntd.0007715
|View full text |Cite
|
Sign up to set email alerts
|

IL-17A, a possible biomarker for the evaluation of treatment response in Trypanosoma cruzi infected children: A 12-months follow-up study in Bolivia

Abstract: BackgroundThe National Program for Chagas disease was implemented in Bolivia in 2006, and it greatly decreased the number of infections through vector control. Subsequently, a treatment regimen of benznidazole (BNZ) was started in seropositive school-age children living in certified vector control areas.Methods and findingsWe conducted a 12-month follow-up study and seven blood samples were taken during and after the treatment. Serology, conventional diagnostic PCR (cPCR) and quantitative Real-time PCR (qPCR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 54 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…Another important point is that in functionally normal patients, their EVs also led to a decrease in IL-17. A follow-up study in school-aged children with Chagas disease found that higher IL-17A levels were associated with the persistence of infection after treatment with benznidazole, suggesting this cytokine could be a possible biomarker for nonresponse to treatment and the persistence of infection [ 54 ]. However, when we analyzed our data under this hypothesis, in contrast to what was previously described, EVs from chronic patients with no cardiac function loss induced a lower production of IL-17, suggesting that in patients who did not receive benznidazole treatment, this cytokine might have another role, even a protective one.…”
Section: Discussionmentioning
confidence: 99%
“…Another important point is that in functionally normal patients, their EVs also led to a decrease in IL-17. A follow-up study in school-aged children with Chagas disease found that higher IL-17A levels were associated with the persistence of infection after treatment with benznidazole, suggesting this cytokine could be a possible biomarker for nonresponse to treatment and the persistence of infection [ 54 ]. However, when we analyzed our data under this hypothesis, in contrast to what was previously described, EVs from chronic patients with no cardiac function loss induced a lower production of IL-17, suggesting that in patients who did not receive benznidazole treatment, this cytokine might have another role, even a protective one.…”
Section: Discussionmentioning
confidence: 99%